Initial experience and establishment of a hypersomnia board: A multidisciplinary approach to complex hypersomnia cases - Mallampalli, Antara; Agrawal, Ritwick; Singh, Supriya; Dang, Lequan; Moghtader, Shahram; Velamuri, Kanta; Thomas, Tara; Sharafkhaneh, Amir (Sleep medicine, 2025)
Hypersomnia disorders are complex both diagnostically and management wise. Complex medical conditions benefit from multidisciplinary board (MDB). We describe the structure, implementation, and preliminary outcomes of a hypersomnia MDB established to improve diagnosis and management of complex hypersomnia cases. We implemented a monthly virtual case-based conference at a large VA medical center, involving clinicians from sleep medicine, psychiatry, neurology, clinical psychology, and pharmacy. Patients with central hypersomnia disorders, diagnostic uncertainty, or management challenges were selected for discussion. Presenting providers summarized patient histories, diagnostics, and treatment concerns. A multidisciplinary group reviewed each case, and consensus recommendations were documented in the electronic health record. Over two years, 33 unique patients were presented. Final diagnoses included narcolepsy type 1 (9/33), narcolepsy type 2 (9/33), idiopathic hypersomnia (6/33), and primary obstructive sleep apnea (6/33). Comorbid mental illness (e.g., depression in 15/33, post-traumatic stress disorder or PTSD in 9/33) and obstructive sleep apnea (18/33) were common. The board recommended medication changes in 8/33 patients, mental health referrals in 5/33, and further diagnostic testing in 8/33. Clinician feedback indicated improved diagnostic clarity, enhanced collaboration, and educational benefit, especially for sleep medicine trainees. Establishing a hypersomnia MDB is feasible and promotes collaborative care, improves diagnostic accuracy and treatment plans for patients with complex hypersomnia, and enhances trainee education. Future directions include measuring treatment outcomes, assessing care barriers, tracking clinical responses over time, and expanding to larger scale operations. •Diagnosis and management of central disorders of hypersomnolence require a multidisciplinary approach that may not be readily available.•Multidisciplinary boards (MDB) may provide a feasible model to care for these patients.•Our preliminary experience showed that hypersomnia-MDB can improve diagnosis and care of these patients.•We need to determine feasibility, cost, and value in care of patients with central disorders of hypersomnolence. Diagnosis and management of narcolepsy and other central disorders of hypersomnolence pose a significant challenge and require multi-disciplinary approach. We implemented a multispecialty board to improve diagnosis and management of patients referred to our sleep center for central disorders of hypersomnolence. The board consisted of specialist in sleep medicine, psychiatry, neurology, clinical psychology, and clinical pharmacy, as well as fellows in training. Our preliminary experience suggests that such an approach results in improved diagnosis, additional referral, additional testing and change in pharmacotherapy.